Presenting cypriot cultural heritage in virtual reality: A user evaluation - Loizides, Fernando; El Kater, Alexios; Terlikas, Constantinos; Lanitis, Andreas; Michael-Grigoriou, Despina (My University, 2014)
This paper presents a user evaluation related to the overall experience of a number of volunteers obtained by visiting two virtual museums populated with digitized Cypriot cultural heritage/art items using different virtual reality display systems. The two virtual museums used are replicas of an engraving museum and a virtual Byzantine icons museum. During the experiment visitors were able to use a Head Mounted Display or a stereoscopic Powerwall projection in order to obtain an immersive 3D experience. The results of the user evaluation indicate that both ways of presenting the museum received an equal usability score among the users but at the same time a number of drawbacks of each method were indicated. The findings of the research are crucial in enabling the use of a user-centered design process approach to improve the prototypes and develop virtual experiences for additional museums. The ultimate aim of our approach is to develop applications that showcase Cypriot Cultural Heritage in a way that attracts visitors to visit the original museums.
Keywords: Cultural heritage; User experience; Virtual museums